PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN SUKARELA PERUSAHAAN MANUFAKTUR - Riznawaty, Nur Fitri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The voluntary disclosure is the types of information which are not required by the capital market supervisory board to be revealed. Voluntary disclosure index is a number that indicates the completeness of voluntary items presented in the companyâs annual report. This research is conducted in manufacturing companies which are classified as the chemicals and basic industries, various industries, and consumer goods industries which are listed in the Indonesia Stock Exchange in 2011. The multiple regressions analysis is applied as the analysis technique in this research. The result of research findings indicate that ownership concentrate, the size of the company, the proportion of independent commissioners and the public accountant office specialized in industries simultaneously have significant influence to the voluntary disclosure of manufacturing industry companies which are listed in the Indonesia Stock Exchange in 2011. The partial influence indicates that only ownership concentrate, the size of the company, and the public accountant office specialized in industries variables which have significant influence to the voluntary disclosure. While, the proportion of independent commissioners has no significant influenceKeywords: Voluntary Disclosure, Voluntary Disclosure Index, Agency Theory, Good Corporate Governance